PENYELENGGARAAN FUNGSI DAN WEWENANG LEMBAGA BAITUL MAL DALAM PENGELOLAAN ZAKAT DI KABUPATEN ACEH BARAT [Studi Implementasi Qanun 10 tahun 2018 tentang Baitul Mal] - Budi Handoyo (Jurnal Sains Riset, 2021)
Qanun Number 10 of 2018 concerning Baitul Mal is the legal basis for the Baitul Mal to carry out its functions and authorities in managing and managing zakat, waqaf, and religious assets. However, the functions and authority of the Baitul Mal have not been fully implemented, including the lack of socialization from the Baitul Mal so that there are still muzaki who do not submit their zakat to Baitul Mal, in collecting and utilizing zakat there are still many obstacles faced by Baitul Mal. The obstacles faced in the management of zakat by Baitul Mal Aceh include inadequate quality of implementing human resources, capacity, inadequate organizational structure, regulatory aspects that are not in line between regional levels and aspects of socialization and institutional understanding of the community. The efforts made by Baitul Mal to overcome the obstacles faced in the management of zakat are preparing implementing regulations from the Aceh Qanun regarding Baitul Mal, strengthening institutions and personnel (capacity building), expanding the socialization of the roles and functions of Baitul Mal Aceh, Regency / City Baitul Mal and Baitul Village mall, and build cooperation and coordination with all related agencies.